Handbook of microbial nanotechnology - Hussain, Chaudhery Mustansar (Academic Press, an imprint of Elsevier, 2022)
Handbook of Microbial Nanotechnology is a collection of the most recent scientific advancements in the fundamental application of microbial nanotechnology across various sectors. This comprehensive handbook highlights the vast subject areas of microbial nanotechnology and its potential applications in food, pharmacology, water, environmental remediation, etc. This book will serve as an excellent reference handbook for researchers and students in the food sciences, materials sciences, biotechnology, microbiology and in the pharmaceutical fields.Microbial nanotechnology is taking part in creating development and innovation in various sectors. Despite the participation of microbial nanotechnology in modern development, there are some hindrances. The lack of information, the possibility of adverse impacts on the environment, human health, safety and sustainability are still a challenge. This handbook addresses these challenges.